High performance surface plasmon resonance based sensor using black phosphorus and magnesium oxide adhesion layer - Kumar, Shatrughna; Yadav, Archana; Malomed, Boris A. (Frontiers in Materials, 2023)
A five layered Kretschmann configuration-based novel structure is designed for a highly sensitive surface plasmon resonance (SPR) sensor. An adhesion layer of magnesium oxide (MgO) is employed on the BK7 prism to avoid the adverse effects of metallic layers which causes SPR broadening and a decrease in the resonance magnitude. A few layers of black phosphorus (BP) on top of silver (Ag) metal layer are added to complete the structure that becomes BK7/MgO/Ag/BP configuration. The investigation is carried out using attenuated total reflection (ATR) while the widely used transfer matrix method (TMM) is applied to evaluate the performance of the SPR sensor. A separate analysis is performed using three thicknesses 5 nm, 10 nm, and 15 nm of MgO, an optimized thickness of 40 nm of Ag, and eight layers of BP. The results revealed that the configuration BK7/MgO(10nm)/Ag(40nm)/BP (8 layers) delivers maximum sensitivity(S) of 234ºRIU-1. Moreover, the configuration BK7/MgO (5 nm)/Ag (40 nm)/BP (8 layers) is delivering a maximum figure of merit (FOM) of 38.18 RIU-1. With this kind of extraordinary features, it is expected the proposed SPR sensor can be applied in different fields of biosensing to detect samples.